An Empire Gone Bad: Agatha Christie, Anglocentrism and Decolonization. (15th March 2018) - Prior, Christopher
Abstract: Recent scholarly accounts of early post-war society have emphasised the importance of positive and self-congratulatory narratives of decolonisation – whereby the end of empire was the inevitable result of a pro-active British beneficence – or have suggested that society was shielded from a sense of imperial decline. Such accounts are complicated by Agatha Christie's immensely popular crime novels, which constructed a narrative of British decline rooted in a sense of departure from pre-war ideals of imperial masculinity, but whose Anglocentrism nevertheless offered up the potential for imperial renewal pending a 'rediscovery' of such characteristics.